IMPLEMENTASI SISTEM KEHADIRAN BERBASIS RADIO FREQUENCY IDENTIFICATION DAN SMART CARD MENGGUNAKAN WEB SERVER - ODI NURDIAWAN; TOMAS TOMAS; ARIA PRATAMA (Jupiter: Journal of Computer & Information Technology, 2021)
This study aims to implement a Radio Frequency Identification attendancean application that is integrated with the database to support the program to improve the disciplined attitude of the teachers of the Nurul Huda Jannatu Vocational High School Cirebon City. This Radio Frequency Identification application consists of several main components, namely id cards which are used to read the information regarding the presence of teachers of the Nurul Huda Jannatu Vocational High School Cirebon City. Database integration in this system will allow data to be automatically stored directly into a Web Server database so that the reach of information can be accessed anywhere without being limited by distance or time and does not need intensive supervision so that the tool facilitates and makes teacher activities more efficient